2012
DOI: 10.3329/bjsir.v47i2.11457
|View full text |Cite
|
Sign up to set email alerts
|

In vitro micropropagation of pointed gourd (Trichosanthes dioica Roxb.) from shoot tip and nodal segment

Abstract: An efficient protocol was developed for plant regeneration, multiplication and rooting under in vitro condition in pointed gourd. Highest percent of shoot regeneration was 91.66%, when nodal explants were cultured on MS+1.0 mg/1 BAP. The maximum number of shoots (4.8) per explant was observed in MS + 1.0 mg/1 BAP + 0.2 mg/1 NAA from nodal segment. Among the two explants, nodal segment was found better for shoot regeneration and multiplication. The best response towards root induction was achieved on half MS me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Similar results were found by Canli and Tian [31] in Prunus salicina Lind1. In contrast, Thomas and Sreejesh [32], and Huq et al [33] working respectively on ash gourd (Benincasa hispida L.) and pointed gourd (Trichosanthes dioica Roxb.) noticed the variation in shoot induction and plant micropropagation according to BAP concentrations.…”
Section: Effects Of 6-benzylaminopurine (Bap) Concentrationmentioning
confidence: 98%
“…Similar results were found by Canli and Tian [31] in Prunus salicina Lind1. In contrast, Thomas and Sreejesh [32], and Huq et al [33] working respectively on ash gourd (Benincasa hispida L.) and pointed gourd (Trichosanthes dioica Roxb.) noticed the variation in shoot induction and plant micropropagation according to BAP concentrations.…”
Section: Effects Of 6-benzylaminopurine (Bap) Concentrationmentioning
confidence: 98%
“…Among these, stem segments are frequently employed to induce cluster buds. Huq et al (2012) observed that when treating the stem tips and stem segments of Trichosanthes dioica Roxb. under the same medium conditions, the regeneration, proliferation, and elongation of stem segments were superior to those of stem tips.…”
Section: Bud Induction In Vitro Culturementioning
confidence: 99%